Amazon Mechanical Turk and the commodification of labour. (November 2014) - Bergvall‐Kåreborn, Birgitta; Howcroft, Debra
<x xml:space="preserve">Abstract</x> Crowd employment platforms enable firms to source labour and expertise by leveraging Internet technology. Rather than offshoring jobs to low‐cost geographies, functions once performed by internal employees can be outsourced to an undefined pool of digital labour using a virtual network. This enables firms to shift costs and offload risk as they access a flexible, scalable workforce that sits outside the traditional boundaries of labour laws and regulations. The micro‐tasks of 'clickwork' are tedious, repetitive and poorly paid, with remuneration often well below minimum wage. This article will present an analysis of one of the most popular crowdsourcing sites—Mechanical Turk—to illuminate how Amazon's platform enables an array of companies to access digital labour at low cost and without any of the associated social protection or moral obligation.